Self-Confidence, Learning Motivation and Students Achievement: The Mediating Role of Digital Literacy - Munawaroh Munawaroh; Rachma Fitriati; Susan Febriantina (Universitas Negeri Malang, 2022)
Accomplishing educational goal is challenging during the Covid-19 pandemic, and it has been covered by adopting technology in educational process. This study examines driving factors affecting students’ learning achievement by incorporating some variables including self-confidence and learning motivation. This study also investigates the mediating role of digital literacy. This study was conducted in a vocational school in Jakarta of Indonesia by involving 188 respondents. A path analysis was involved to gain an understanding for this relationship. The findings remark that students’ learning achievement can be explained by self-confidence and learning motivation. This results also confirm the mediating role of digital literacy in understanding the connectivity between variables. Keywords: Learning Motivation, Self-confidence, Digital Literacy, Learning Achievement